Aspectos geográficos, turísticos y políticos que fomentan el desarrollo de un producto ecoturístico binacional Perú - Ecuador - Salas Cubas, Ingrid (2018)
The present investigation denominated geographical, touristic and political_x000D_ aspects that foment the development of an ecotouristic product binational_x000D_ Peru - Ecuador has as objective to determine the geographic, tourist and political_x000D_ aspects that foment the development of an ecotouristic product binational Peru -_x000D_ Ecuador._x000D_ The aspects that promote the development of a Binational Peru - Ecuador_x000D_ ecotouristic product in the geographical part are geography, location criteria and_x000D_ road interconnection; in the tourist part, the existence of a tourist offer, tourist_x000D_ facility, tourist demand and tourist promotion; and in the political sphere, it is_x000D_ conditioned by territorial planning, national and local tourism planning,_x000D_ environmental planning and bi-national regulations._x000D_ In order to obtain the data, the following activities have been carried out;_x000D_ application of the technique of direct observation in the provinces of Piura,_x000D_ Tumbes, Loja and Machala as well as in the natural parts found there; interview_x000D_ addressed to key informants, authorities and researchers, surveys of Peruvian_x000D_ and Ecuadorian tourists; the technique of signing up for the inventory of tourist_x000D_ resources; also instruments such as survey questionnaire and interview, field_x000D_ notebooks and cameras. Both the techniques and the instruments allowed us to_x000D_ obtain adequate information for the preparation of this report.